KAJIAN RANTAI PASOK BERAS DI DISTRIK TANAH MIRING KABUPATEN MERAUKE - Marthen A. I. Nahumury; Maria M. D. Widiastuti (Universitas Musamus, Merauke, Papua, 2015)
This study aims to assess the rice supply chain and analyze the efficiency of rice supply chain in Tanah Miring District. The methodology used a snowball sampling. The sample of respondent consist of 50 farmers in 5 villages, 20 supplier (Rice Milling Unit), 10 trader in medium scale and 10 trader in big scale at Merauke District. The results showed that rice supply chain in Tanah Miring District have a six-channel. Channel one: farmers-end consumers, channel two: farmers-big trader-medium trader-retailer-end consumers, channel three: farmers-big trader-medium trader-end consumers, channel four: farmers-medium trader-retailer-end consumers, channel five: farmers-retailers-end consumers and channel six: farmers-big trader-district logistic agency (Bulog)-end consumers.The efficient channel was channel one, was sell directly to the end consumer.